Releitura nas artes visuais: contribuições à leitura da imagem pictórica nas aulas de Arte do Instituto Federal do Maranhão – Campus Açailândia - PESSOA FILHO, Raimundo Morais (2020)
This dissertation has as object of study the process of analysis of the pictorial image in the scope of Art / Education. The general objective of the research is to analyze the process of critical reflection of the student through the practice of contextualized rereading of pictorial image, from his reading of the world and personal experiences. It proposes ways to integrate the image reading of the pictorial work of art, mediated by the use of specific approaches developed for this purpose, contributing to the identification, translation and mastery of the formal elements and codes typical of the visual language, as well as understanding the structure of the texts visual, characterized by a specific visual grammar. Methodologically, the work is guided by bibliographic research and action research. In addition, the results are analyzed in a qualitative way, as the corpus is formed by the rereadings of the participating students. As a methodological theoretical contribution, we highlight studies on Erwin Panofsky's Iconography / Iconology, Robert Ott's Image Watching System and Ana Mae Barbosa's Triangular Approach / Proposal. We are anchored in these image and Art / Education theorists who emphasize the importance of image reading and the need for visual education. Therefore, these studies and systematizations guide a theoretical / practical work. During the research, we allow ourselves to share knowledge and actions and also acquire new learning from those involved in the process during action research, in order to contribute to the formation of critical, creative readers and proponents of new images that can be read further.